2013
DOI: 10.1111/j.1540-4781.2013.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

An Emergent Perspective on the Use of the First Language in the English‐as‐a‐Foreign‐Language Classroom

Abstract: This study investigates contextual features surrounding the use of a first language (L1) in a Japanese university English‐as‐a‐foreign‐language (EFL) course during peer interaction in the extended preparation phase leading up to two oral presentation tasks (OP1 and OP3), performed seven months apart. Interaction data were analysed in terms of the amount of L1 production, the distribution of L1 use within and across tasks and dyads, and the focus of learner talk. Contextual influences on L1 use were also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 51 publications
(87 reference statements)
5
54
1
Order By: Relevance
“…Statistical findings revealed that there was significant difference between two groups in four components of writing subsequent to L1-based feedback instruction. The findings of the study support a growing body of research (Atkinson, 1987;Moore, 2013;Çelik, 2008;Carless, 2008;etc. ) regarding L1 use in foreign language classes.…”
Section: Discussionsupporting
confidence: 80%
“…Statistical findings revealed that there was significant difference between two groups in four components of writing subsequent to L1-based feedback instruction. The findings of the study support a growing body of research (Atkinson, 1987;Moore, 2013;Çelik, 2008;Carless, 2008;etc. ) regarding L1 use in foreign language classes.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to personality traits, pedagogical knowledge is regarded another important are that distinguishes good language teacher, and private language courses appear to have a strong consensus on the importance of classroom management skills, an ongoing professional development, skill integration, enhancement of learner autonomy, and transfer of input appropriately. However, they made the point of L2 usage forcibly, stating that mother tongue usage is not natural in language classrooms (Moore, 2013). When it comes to subject-knowledge aspect, it was found that especially having a sound knowledge of grammar and vocabulary is what distinguishes a good language teacher, and this tendency could be explained with the exam-driven Turkish education system in which exams basically test students' grammar knowledge and reading skills.…”
Section: Resultsmentioning
confidence: 99%
“…In different pedagogical settings, however, some educators believe that L1s should be used judiciously, if not avoided entirely (for a discussion, see, e.g., Cook, 2001;Edstrom, 2006;Turnbull, 2001). These beliefs are also shared by some learners (e.g., Mora Pablo, Lengeling, Zenil, Crawford, & Goodwin, 2011;Rolin-Ianziti & Varshney, 2008;Storch & Wigglesworth, 2003). This perspective is not, however, shared by all.…”
mentioning
confidence: 89%
“…Despite this, their qualitative data reveals that participants viewed L1 mediation negatively, as it could potentially create a dependence on the L1 and reduce target language exposure. Recently, Mora Pablo et al (2011) elicited FL learners' beliefs about L1 mediation using a fourprompt questionnaire. Learners reported relying on L1 mediation for socializing purposes as well as for vocabulary, grammar, and task management functions; yet L1 mediation was seen as illogical and useless.…”
Section: Learners' Beliefs: a Sociocultural Frameworkmentioning
confidence: 99%